9514 1404 393
Answer:
(2x +1)/(4x^2) . . . . except x=0, -1
Explanation:
Addition of fractions works in the usual way:
a/b +c/d = (ad +bc)/(bd)
Division of fractions works in the usual way:
(a/b)/(c/d) = (ad)/(bc)
__
![(\left((1)/(2x)+(1)/(2x+2)\right))/(\left((2x)/(x+1)\right))=(1)/(2)\cdot(\left((1)/(x)+(1)/(x+1)\right))/(\left((2x)/(x+1)\right))=(1)/(2)\cdot(\left((2x+1)/(x(x+1))\right))/(\left((2x^2)/(x(x+1))\right))\\\\=\boxed{(2x+1)/(4x^2)}](https://img.qammunity.org/2022/formulas/mathematics/high-school/vsep62c84mfqbfvktlk3kx1ommjulvstbv.png)
The expression is undefined for any denominator equal to zero: x=0 or x=-1.